PERPHERAL BLOOD CELL MITOCHONDRIAL DYSFUNCTION IN MYELODYSPLASTIC SYNDROMECAN BE IMPROVED BY A COMBINATION OF COENZYME Q10 AND CARNITINE: Blood cell mitochondrial dysfunction in myelodysplastic syndrome - Filanovsky, Kalman; Haran, Michal; Mirkin, Vita; Braester, Andrei; Shevetz, Olga; Stanevsky, Anfisa; Sigler, Erica; Votinov, Ekaterina; Zalzman-Amir, Yehudit; Berrebi, Alain; Gross, Atan; Shvidel, Lev (Mediterranean Journal of Hematology and Infectious Diseases, 2020)
Structural mitochondrial abnormalities as well as genetic aberrations in mitochondrial proteins have been known in Myelodysplastic syndrome (MDS) , yet there is currently little data regarding the metabolic properties and energy production of MDS cells. In the current study we used state-of-the-art methods to assess OXPHOS in peripheral blood cells obtained from MDS patients and healthy controls We then assessed the effect of food supplements- Coenzyme Q10 and carnitine on mitochondrial function and hematological response .We show here for the first time that in low risk MDS there is a significant impairment of mitochondrial respiration in peripheral blood cells and this can be improved with food supplements. We also show that such myelodysplastic syndrome, mitochondria, oxidative phosphorylation, coenzyme Q10, seahorse XF analyzer. supplements lead to improvement in cytopenia's and quality of life.